2014
DOI: 10.1016/j.theriogenology.2014.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Long-term and transgenerational effects of cryopreservation on rabbit embryos

Abstract: ElsevierLavara García, R.; Baselga Izquierdo, M.; Marco Jiménez, F.; Vicente Antón, JS. (2014). Long-term and transgenerational effects of cryopreservation on rabbit embryos. Theriogenology. 81 (7) This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 29 publications
1
20
0
1
Order By: Relevance
“…Some authors postulate that these procedures do not induce major anomalies but can lead to morphologic and behavioral features in adult mice derived from frozen embryos [16]. However, Auroux et al [17] found a beneficial effect in longevity in adults, and Lavara et al [22] reported a positive long-term effect on reproduction traits in rederived rabbit females from vitrified embryos, probably due to changes in epigenetic control regions related with reproductive traits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some authors postulate that these procedures do not induce major anomalies but can lead to morphologic and behavioral features in adult mice derived from frozen embryos [16]. However, Auroux et al [17] found a beneficial effect in longevity in adults, and Lavara et al [22] reported a positive long-term effect on reproduction traits in rederived rabbit females from vitrified embryos, probably due to changes in epigenetic control regions related with reproductive traits.…”
Section: Discussionmentioning
confidence: 99%
“…However, Auroux et al [17] found a beneficial effect in longevity in adults, and Lavara et al [22] reported a positive long-term effect on reproduction traits in rederived rabbit females from vitrified embryos, probably due to changes in epigenetic control regions related with reproductive traits. Values in the same row with different superscript are significantly different (P < 0.05).…”
Section: R Lavara Et Al / Theriomentioning
confidence: 99%
See 1 more Smart Citation
“…Vitrification also affects foetal survival and growth and modifies the placental development at term [60,76] and growth from birth to adult age [77]. Nonetheless, positive long-term effects of cryopreservation and transfer procedures on female offspring reproduction have been reported, namely in the litter size and the number of newborns alive at birth [78].…”
Section: Embryo Cryopreservationmentioning
confidence: 99%
“…A good understanding of the chronology of events that follows the ovulation is crucial to the recovery of preimplantation embryos [78]. At 24 hpc, all the embryos can be found in the isthmus [95].…”
Section: Embryo Recovery and Transfermentioning
confidence: 99%